Peningkatan Hasil Belajar Matematika Siswa Kelas II melalui Tipe Teams Assisted Individualization - Rosfiani, Okta; Sahara, Allma; Mustofa, Miftakhul Ilmi; Effendy, Lukman; Furqon, Sayyid Ali (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
By using the Teams Assisted Individualization (TAI) learning approach, this study seeks to enhance the learning results of second-grade pupils in mathematics. TAI is a kind of cooperative learning that allows students to study based on their unique learning styles by fusing solo and group projects. It is anticipated that this model will enhance students' comprehension of fundamental mathematical ideas, particularly addition and subtraction. This study is a case study that was carried out at SDN Pondok Ranji 04 using a two-cycle classroom action research (PTK) methodology. Planning, action implementation, observation, and reflection were the four phases that made up each cycle. Student surveys, learning outcome assessments, and observation were used to gather data. The findings demonstrated that using the TAI model greatly enhanced student learning outcomes. Although it had not yet reached 80%, the growth from cycle I was carried over to cycle II. The TAI model's implementation in cycle II was successful in raising learning outcomes to 90.2%. This result demonstrates that the TAI model works well for both enhancing learning outcomes and fostering a more engaging and joyful learning environment.